Pengaruh Dimensi Budaya Hofstede Terhadap Deviant Workplace Behavior. Studi Pada Karyawan Kantor Pelayanan Pajak Pratama Singosari - Dewi Faikhotul Himmah (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect  of  Hoftede cultural dimensions simultaneously or partially on deviant workplace behavior to  Pratama Singosari Tax Office’s employees . This type of research used in this research is explanatory research to study the  effect of independent variables, namely  power distance, collectivism/individualsm, masculinity/feminimity, uncertainty avoidance  and the dependent variable is workpace deviant behavior. The research instrument used was a questionnaire. Data analysis tool used in this study  is a multiple linear regression, which includes the classic assumption test, multicollinearity test, normality test, and  heterokedastisitas  test. As for testing the hypothesis include the F test and t test. Results showed variable  power distance, collectivism /individualsm, masculinity/feminimity,  partially contained  is not  significant influence  on  the workpace deviant behavior. As for the variable  uncertainty avoidance partially contained significant influence on deviant behavior workpace. Key words :Power Distance,Collectivism/individualsm, Masculinity/feminimity,  Uncertainty avoidance,  deviant workpace behavior.